Análise quimico-farmacêutica de Darunavir etanolato em comprimidos e de seu complexo de inclusão - Kogawa, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The work aimed the formation of complex darunavir:β-cyclodextrin and the study of the consequences of complexation, as well as development and validation of analytical methods for qualitative and quantitative determination of darunavir in tablet (free) and complexed to β-cyclodextrin. darunavir free. The form of darunavir ethanolate was monitored throughout research time to ensure use of the same polymorph and no analytical differences. Qualitative analysis was performed by thin layer chromatography (TLC), ultraviolet spectrophotometry (UV), infrared spectroscopy (IR), liquid chromatography (LC) and capillary electrophoresis (CE) allowing the identification of darunavir ethanolate in tablets. More dynamic and environmentally friendly methods were validated for the quantification of darunavir ethanolate in pharmaceutical form using the IV and CE. The results of the validations were comparatively analyzed and techniques were equivalent and are therefore interchangeable. darunavir:β-ciclodextrina. Darunavir was complexed with β- cyclodextrin and confirmed by thermal techniques and studied by spectroscopic methods. Its properties were compared to the free drug as to solubility of inclusion complex and it is 28 times more soluble than darunavir when using buffer solution of 0.05 M acetate pH 4.5. This advance of pharmaceutical technology covers the resolution Best medicines for children discussed in the World Health Assembly, which launched the global campaign Make medicines child size. A method for quantification of darunavir in the complex was validated by LC coupled with mass spectrometry (LC-MS), with him were identified six degradation products, two from acid degradation, one from basic degradation and three from oxidative degradation. A developed TLC technique was adequate for visualizing all degradation products of complex darunavir:β-cyclodextrin observed in the CL method, being achieved faster and cheaper. Complex ...

O trabalho objetivou a formação do complexo darunavir:β-ciclodextrina e o estudo das consequências desta complexação, além do desenvolvimento e validação de métodos analíticos para determinação qualitativa e quantitativa do darunavir em comprimidos (livre) e complexado à β-ciclodextrina. darunavir livre. Durante todo o tempo de pesquisa a forma etanolato do darunavir foi controlada para garantir o uso do mesmo polimorfo e não haver diferenças analíticas. As análises qualitativas foram realizadas por cromatografia em camada delgada (CCD), espectrofotometria no ultravioleta (UV), espectrofotometria no infravermelho (IV), cromatografia líquida (CL) e eletroforese capilar (EC) possibilitando a identificação do darunavir etanolato em comprimidos. Métodos mais dinâmicos e ecologicamente corretos foram validados para a quantificação do darunavir etanolato na forma farmacêutica utilizando o IV e a EC. Os resultados das validações foram analisados comparativamente e as técnicas mostraram-se equivalentes sendo, portanto, intercambiáveis. darunavir:β-ciclodextrina. O darunavir foi complexado à β-ciclodextrina e confirmado através de técnicas térmicas e estudado por métodos espectroscópicos. Suas propriedades foram comparadas às do fármaco livre quanto à solubilidade e o complexo de inclusão mostrou ser 28 vezes mais solúvel que o darunavir quando utilizada a solução tamponante acetato 0,05 M pH 4,5. Este avanço da tecnologia farmacêutica abrange a resolução Best medicines for children discutida na Assembleia Mundial da Saúde, a qual lançou a campanha global Make medicines child size. Um método para quantificação de darunavir no complexo foi validado através da CL acoplada à espectrometria de massas (CL-EM), nele foram identificados seis produtos de degradação sendo dois provenientes da degradação em meio ácido, um da degradação em meio básico e três em meio oxidativo. Uma técnica ...
Keywords: Solubilidade; Ciclodextrinas; Fármacos; Tecnologia farmacêutica; Química farmacêutica; Pharmaceutical technology